(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the phenomenon of the disputatious or misinterpretation of Quranic verses by deviant movements and extremist groups throughout Islamic history and in the contemporary era. The study identifies the principal causes of misinterpretation including religious illiteracy, malicious ideological intent, and hyper-literalism and classifies the most commonly misused categories of Quranic verses. Specific cases are analysed: the use of Surah Ali ‘Imran 3:104 by Hizb ut-Tahrir to justify a political movement; the use of Surah an-Najm 53:39 to deny the transmission of spiritual reward to the deceased; the use of Surah al-An’am 6:57 and al-Ma’idah 5:44 by Kharijite- inspired groups to condemn modern governance as unbelief; and the exploitation of verses on jihad, emigration (hijrah), and relations with non-Muslims to incite violence and social division. For each case, the article presents the scholarly response grounded in the classical methodology of tafsir, the reasons for revelation (asbab al-nuzul), and the consensus of Ahl al-Sunnah. The article concludes that countering misinterpretation requires the promotion of methodologically rigorous exegesis and the transmission of the classical scholarly tradition to new generations.